2014
DOI: 10.1016/j.reprotox.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Soy but not bisphenol A (BPA) induces hallmarks of polycystic ovary syndrome (PCOS) and related metabolic co-morbidities in rats

Abstract: Polycystic ovarian syndrome (PCOS) is the most common female endocrine disorder with a prevalence as high as 8–15% depending on ethnicity and the diagnostic criteria employed. The basic pathophysiology and mode of inheritance remain unclear, but environmental factors such as diet, stress and chemical exposures are thought to be contributory. Developmental exposure to endocrine disrupting compounds (EDCs) have been hypothesized to exacerbate risk, in part because PCOS hallmarks and associated metabolic co-morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 72 publications
2
34
0
Order By: Relevance
“…While there were no significant diet effects on ovary weights, there was a higher incidence of gross ovarian cysts in the three low isoflavone diets compared to the NIH-41 diet. Patisaul et al (2014) recently reported an increased incidence of cystic follicles in Wistar rats fed a soy meal containing diet.…”
Section: Discussionmentioning
confidence: 99%
“…While there were no significant diet effects on ovary weights, there was a higher incidence of gross ovarian cysts in the three low isoflavone diets compared to the NIH-41 diet. Patisaul et al (2014) recently reported an increased incidence of cystic follicles in Wistar rats fed a soy meal containing diet.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of kisspeptin expression -In vitro: Klenke et al, 2016-In vivo: Cao et al, 2012Navarro et al, 2009;Xi et al, 2011;Naulé et al, 2014;Kurian et al, 2015 Alteration in GnRH and/or LH secretion -In vivo: Monje et al, 2010;Fernández et al, 2009;Viega-Lopez et al, 2014;Kurian et al, 2015 Alteration of estrous cyclicity -In vivo: Honma et al, 2002;Nikaido et al, 2004;Wang et al, 2014a;Rubin et al, 2001;Mendoza-Rodríguez et al, 2011;Patisaul et al, 2014;Delclos et al, 2014;Nah et al, 2011;Adewale et al, 2009;Fernández et al, 2009;Zaid et al, 2014 Table 8 provides an overview of the critical elements in the identification of an endocrine disruptor and how they are fulfilled for alteration of estrous cycle by BPA.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior study with a similar design, we showed that a soy-rich diet (Purina 5001) generating approximately 20 ng/ml (74 nM) free GEN levels in the dams [50], promoted early VO, weight gain, elevated baseline glucose levels and increased area under the curve in the classic glucose challenge test [78]. Isoflavone levels in the custom diet for the present study were 400 mg/kg, and produced dam serum GEN levels in the range of 2.8–31 ng/mL.…”
Section: Discussionmentioning
confidence: 99%